Neurochemical changes following combined hypoxemia and hemorrhagic shock in a rat model of penetrating ballistic-like brain injury: A microdialysis study. Issue 5 (November 2016) - Leung, Lai Yee; Deng-Bryant, Ying; Cardiff, Katherine; Winter, Megan; Tortella, Frank; Shear, Deborah
Abstract : BACKGROUND: Energy metabolic dysfunction is a key determinant of cellular damage following traumatic brain injury and may be worsened by additional insults. This study evaluated the acute/subacute effects of combined hypoxemia (HX) and hemorrhagic shock (HS) on cerebral interstitial levels of glucose, lactate, and pyruvate in a rat model of penetrating ballistic-like brain injury (PBBI). METHODS: Rats were randomly assigned into the sham control, PBBI, and combined injury (P + HH) groups. The P + HH group received PBBI followed by 30-minute HX and 30 minute HS. Samples were collected from striatum (perilesional region) using intracerebral microdialysis at 1 to 3 hours after injury and then at 1 to 3, 7, and 14 days after injury. Glucose, lactate, and pyruvate were measured in the dialysate samples. RESULTS: Glucose levels dropped significantly up to 24 hours following injury in both PBBI and P + HH groups ( p < 0.05). A reduction in pyruvate was observed in the PBBI group from 24 to 72 hours after injury (vs. sham). In the P + HH group, the pyruvate was significantly reduced from 2 to 24 hours after injury ( p < 0.05 vs. PBBI). This prominent reduction persisted for 14 days after injury. In contrast, lactate levels were significantly increased in the PBBI group during the first 24 hours after injury and remained elevated out to 7 days. The P + HH group exhibited a similar trend of lactate increase as did the PBBI group. Critically, P + HH further increased the lactate-to-pyruvate ratio by more than twofold (vs. PBBI) during the first 24 hours. The ratio reached a peak at 2 hours and then gradually decreased, but the level remained significantly higher than that in the sham control from 2 to 14 days after injury ( p < 0.05). CONCLUSION: This study identified the temporal profile of energy-related neurochemical dysregulation induced by PBBI and combined injury in the perilesional region. Furthermore, combined HX and HS further reduced the pyruvate level and increased the lactate-to-pyruvate ratio following PBBI, indicating the exacerbation of posttraumatic metabolic perturbation.